International Conference on Transportation and Development 2019. selected papers from the International Conference on Transportation and Development 2019, June 9-12, 2019, Alexandria, Virginia - Noyce, David A. 1961- (American Society of Civil Engineers, 2019)
Selected papers from the International Conference on Transportation and Development 2019, held in Alexandria, Virginia, June 9-12, 2019. The collection contains 17 peer-reviewed papers on innovation and sustainability in smart mobility and smart cities. Topics include: tracking and sensing vehicles in smart mobility; accessibility in smart cities; new energy in smart mobility; air transportation and unmanned aerial vehicles; and international topics in smart mobility. This proceedings will be of interest to practitioners, planners, researchers, and policymakers in a broad area of smart transportation and development.
Sponsored by the Transportation & Development Institute of ASCE.
Keywords: Traffic engineering -- Congresses.; Traffic monitoring -- Congresses.; Traffic flow -- Congresses.; Traffic congestion -- Prevention -- Congresses.; Intelligent transportation systems -- Congresses.; Smart cities -- Congresses.; Sustainable urban development -- Congresses.; elektronické knihy; electronic books